VEGETATION PYRAMIDS APPLIED TO THE ANALYSIS OF DENSE FOREST UNITS IN THE PANTANAL OF ABOBRAL - Sakuma, Mariane Zambone; Hall, Climbiê Ferreira; da Silva, Mauro Henrique Soares (Ra’e Ga: o Espaço Geográfico em Análise, 2020)
The Pantanal of Abobral consists of units of heterogeneous landscapes, in which some dense vegetation, popularly known as cordilheiras and capões, stand out and survive amidst the floodplain. Such formations are of great importance for local biodiversity, but are continually exploited by livestock without adequate management. The aim of this study is to graphically demonstrate the process by which a cordilheira has been going through and discuss the possible causes of environment degradation related to the composition of each vegetal stratum. Biogeographic data sheets were filled with information from the herbaceous, shrubby and arboreal strata, collected in three plots, two at the edges and one at the center of the cordilheira. Strata information were graphically compiled in three vegetation pyramids, visually demonstrating the dynamics of the strata, providing a comparative analysis of the plots from aspects related to dynamics and sociability. Nineteen species, of various strata, were recorded in the central plot, compared to 13 and 15 species in the edges. The most frequent species in all plots was Attalea phalerata. The species composition of the cordilheira, indicated the occurrence of adaptive processes in response to biotic, abiotic and anthropic factors such as laminar erosion, burnings and presence of cattle. An analysis of the vegetation pyramids corroborated the field observations, due to the progression of the arboreal stratum and low representativeness of the other strata.